Analisis Dimension dengan Keyword Isra Mi’raj menggunakan Teknik Blibliometrik - Dzul Adli Muzhoffar Al Arifi (Gunung Djati Conference Series, 2023)
This study aims to analyze the dimensions with the keyword isra mi’raj. This study uses a bibliometric dimensions technique. The formal object of this study is dimensions, while the material object is dimensions analysis with the keyword isra mi’raj. The results and discussion of this study indicate that there are four categories in the mapping research of isra mi’raj. First, the research category in the publication of articles on isra mi’raj. Second, the development of publications (overview) regarding isra mi’raj. Third, researchers who play an active role in isra mi’raj. And fourth, the publication places that dominate publications regarding isra mi’raj.